2018
DOI: 10.3174/ajnr.a5824
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Vessel Wall MR Imaging for Follow-Up after Stent-Assisted Coil Embolization of Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE: Follow-up with MRA for intracranial aneurysms after stent-assisted coiling is complicated by imaging artifacts. We evaluated the usefulness of an alternative method: vessel wall MR imaging. MATERIALS AND METHODS: We conducted a single-center, retrospective review of medical records of 47 patients who underwent 3D TOF-MRA, vessel wall MRI, and DSA after stent-assisted coiling between March 2016 and January 2018. We evaluated the mean value of the signal intensity in the stented artery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Specifically in the case of aneurysms, emerging interest in VWI as a biomarker of aneurysm wall integrity has supported its use to identify aneurysms at high risk of rupture, to surveil aneurysms, or to remove uncertainty about the source of hemorrhage and to identify culprit aneurysms preoperatively 2 3. VWI is particularly well suited to longitudinal characterization in light of its non-invasive nature, potentially obviating the need for invasive catheter angiographic monitoring; however, past studies have focused primarily on the characterization of treatment-naïve, unruptured, and ruptured aneurysms while its usefulness for treated aneurysms remains mostly unexplored or restricted to limited series 4–7. We recently have implemented a custom-optimized black-blood VWI for characterization of treated aneurysms, with particular attention paid to the imaging evolution of aneurysms following flow diversion, now widely considered as the first-line treatment for aneurysms of varying subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in the case of aneurysms, emerging interest in VWI as a biomarker of aneurysm wall integrity has supported its use to identify aneurysms at high risk of rupture, to surveil aneurysms, or to remove uncertainty about the source of hemorrhage and to identify culprit aneurysms preoperatively 2 3. VWI is particularly well suited to longitudinal characterization in light of its non-invasive nature, potentially obviating the need for invasive catheter angiographic monitoring; however, past studies have focused primarily on the characterization of treatment-naïve, unruptured, and ruptured aneurysms while its usefulness for treated aneurysms remains mostly unexplored or restricted to limited series 4–7. We recently have implemented a custom-optimized black-blood VWI for characterization of treated aneurysms, with particular attention paid to the imaging evolution of aneurysms following flow diversion, now widely considered as the first-line treatment for aneurysms of varying subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…For 3D-TOF MRA, shielding artifacts reportedly have a larger effect on the signal of the stented artery than susceptibility artifacts. 16 However, since a previous study of VWI using the same method as that used in the present study reported that an in-stent thrombus could be visualized, 14 we consider that our BB-MRA findings generated from VWI correspond to the black-blood imaging of blood flow, and not a loss in signal arising from RF shielding artifacts. Additionally, our literature search revealed no reports on RF shielding artifacts in VWI data.…”
Section: Discussionmentioning
confidence: 58%
“…However, our study did not include these cases. Kim et al 14 reported that an in-stent thrombus could be visualized using VWI. Therefore, we consider that our study of BB-MRA generated VWI would have been more convincing with the addition of cases of instent stenosis and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be an effective non-invasive imaging method for assessing the risk of aneurysm rupture. Black blood MR imaging can clearly display the vascular wall as low signals by reducing the blood flow effect (27). Compared to HR-MRI technology that had limited scanning ranges and long image acquisition times, 3D T1-SPACE uses isotropic volume scanning for 3D high-resolution reconstruction at any level.…”
Section: Discussionmentioning
confidence: 99%